2019
DOI: 10.5152/tjar.2019.95770
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fasting Times for Patients Undergoing Caesarean Delivery: Before and After a Patient Educational Initiative

Abstract: Objective: Prolonged preoperative fasting may lead to dehydration, hypoglycaemia, ketoacidosis and delayed recovery. We hypothesised that a patient educational initiative would decrease our preoperative fasting periods for elective caesarean delivery. Methods: This was an observational quality improvement impact study. Elective caesarean patients who delivered during our study period were included in the study, 40 patients in the pre-intervention and 40 patients in the post-intervention groups. Only English-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…This means that the actual fasting times for both decreased significantly, but only the actual fasting time for clear fluids decreased by a clinically relevant extent. These findings are in line with an educational initiative carried out with patients undergoing elective caesarean delivery [ 7 ]. In this study by Yurashevich et.al ., the actual fasting time for fluids decreased from 10 (8.9–12) h to 3.5 (2.5–10) h after introducing an educational pamphlet for patients including the recommended fasting times, while the actual fasting time for solids did not change significantly [ 7 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This means that the actual fasting times for both decreased significantly, but only the actual fasting time for clear fluids decreased by a clinically relevant extent. These findings are in line with an educational initiative carried out with patients undergoing elective caesarean delivery [ 7 ]. In this study by Yurashevich et.al ., the actual fasting time for fluids decreased from 10 (8.9–12) h to 3.5 (2.5–10) h after introducing an educational pamphlet for patients including the recommended fasting times, while the actual fasting time for solids did not change significantly [ 7 ].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, several studies revealed prolonged fasting times as a general problem among adult patients. Despite the current recommendations, actual fasting times of more than 10 h for fluids and 13 h for solids are common [ 7 – 9 , 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rollout of an educational pamphlet regarding preoperative fasting, written in plain language and given to patients on the evening before their elective CDs, has significantly reduced median fasting times for clear fluids in an American study. 9 In that observational quality improvement impact study, the median fasting time for fluids declined from 10 hours (IQR 8.9-12) to 3.5 hours (IQR 2.5-10) after the introduction of the pamphlet (p < 0.001). For various reasons, this study's findings may not be generalisable to the South African situation, and another means of patient education may be more appropriate.…”
mentioning
confidence: 95%